Pengaruh Media Pembelajaran Buku Saku Matakuliah Elektronika Digital Terhadap Minat Belajar Mahasiswa - Rosmiati, Rosmiati; Ruhamah, Ruhamah (Patria Artha Technological Journal, 2022)
The research entitled "The Influence of Digital Electronic Book PocketBook Learning Media on Student Learning Interests" aims to develop and find out the influence of Learning media in the form of Digital Electronic Course PocketBooks used in the learning process as one of the guidelines used by students both in the classroom and outside the classroom. The research method used is the research and development method (Research and Development). The results of the study obtained that the feasibility of learning media for digital electronic subject books can be reviewed from two aspects, namely from the aspect of the quality of digital electronic subject book and material quality. In terms of quality, digital electronic subjectbooks through the feasibility validation test of pocket books get a percentage of 76% or with the category "Worthy" while in terms of material quality is at a percentage of 78.4% or with the category "Feasible". So that the digital electronic subject book is worthy to be used as a learning medium. Meanwhile, the results of the analysis of questionnaires conducted on students were obtained that with the pocket book of digital electronic courses can increase student learning interest by 83.4% with excellent categories